(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Planktonic biomass and physico-chemical properties of water from a lake at Jahangirnagar University, Bangladesh were studied during new moon, first quarter, full moon and last quarter phases from 16th June to 15th July 2015. Twenty four species of phytoplankton belonging to Chlorophyceae, Bacillariophyceae and Euglenophyceae were recorded. Maximum abundance (162-301 unit/l) of Chlorophyceae was recorded in first quarter phase followed by full moon phase (112-224 unit/l), new moon phase (85-222unit/l) and last quarter phase (60-125 unit/l), respectively. Chlorella vulgaris and Biddulphia aurita were the most abundant phytoplankton throughout the lunar period. Among the zooplankton, 5 species of Protozoa, 2 species of Rotifer, 3 species of Cladocera and 1 species of Ostracoda were recorded. Highest zooplankton was recorded in full moon phase (54-105 unit/l) and Daphnia cephalata was the most abundant species throughout the lunar cycle. Physico-chemical parameters indicate that the water temperature, colour, odour and pH were almost similar throughout the lunar cycle, whereas maximum dissolved oxygen (7.16 mg/l) and minimum (4.43 mg/l) were found during the last quarter and the full moon phase, respectively. The highest content of free carbon dioxide (4.36 mg/l) and chloride (22.8 mg/l) were recorded during first quarter and full moon phase accordingly. Jahangirnagar University J. Biol. Sci. 4(2): 31-36, 2015 (December)